Affect and belonging in political uses of the past - Farrell-Banks, David (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"Affect and Belonging in Political Uses of the Past examines key political events of the past decade, to analyse the relationship between the representation of certain pasts in 'official' heritage settings and the use of the same pasts in political discourse. Drawing on data gathered from museums, heritage sites, news articles, political speeches, manifestos, and through digital media such as Twitter, Farrell-Banks demonstrates how a connection with a shared past can move people emotionally and give them the confidence to engage in political action. The book considers how heritage and the past moves in time and space, examining how it shapes political beliefs and action in the present. The work is a timely intervention, calling attention to the political responsibilities that come with heritage work, when these same languages of heritage are adopted to promote a politics of division. Introducing the concept of the 'moving moment', a framework by which to research and understand uses of the past, the book demonstrates how the past becomes a potent political tool. Combining critical heritage studies, critical discourse, memory studies and political theory, the book demonstrates new approaches to interdisciplinary studies within heritage. Affect and Belonging in Political Uses of the Past will thus be essential reading for academics and students engaged in the study of heritage, memory, politics, history and media"--
Affect, Belonging and the Ambiguity of the Past -- Tracking Moving Moments -- Magna Carta in History and Heritage Discourse -- Magna Carta in Political Discourse -- The 1683 Siege of Vienna in History and Heritage Discourse -- The 1683 Siege of Vienna in Political Discourse -- Moving Moments and the Affective Persistence of the Past.
OCLC-licensed vendor bibliographic record.
Keywords: Magna Carta -- Influence; Cultural property -- Political aspects; Cultural property -- Psychological aspects; Collective memory -- Political aspects -- Case studies; Group identity -- Political aspects -- Case studies; Political culture -- Case studies; Vienna (Austria) -- History -- Siege, 1683.; ART / History / General; POLITICAL SCIENCE / General